Contrastive Analysis of Phraseological Units in English and Uzbek Languages - Narmuratov Zayniddin Radjabovich (Euro Asian Journal Publishing, 2024)
Phraseological units are important tools for creating imagery, expressiveness, and emotionality, and they serve to increase the expressive effectiveness of artistic publicist texts. Phraseological units fit the spirit of the period because of their conciseness, semantic weight, and impact. This, in turn, proves once again the relevance and importance of phraseological research at the present time. The collected materials and their analysis can be used in the process of literary translation, as well as in lecturing on the course of English lexicology, practical training and compiling dictionaries. In addition, based on the results of this analysis, words and phrases from other lexical-semantic groups can be studied both functionally and semantically.
Keywords: Unity; fixed compounds; phraseology; semantics